PROSES PIROLOSIS PENGOLAHAN SAMPAH PLASTIK MENJADI BAHAN BAKAR CAIR - Moh. Arif Batutah; Moh. Agus Setiawan; Hadi Kusnanto (Universitas Mulawarman, 2022)
The research aims to utilize polyethylene (PET), polypropylene (PP) and polystyrene (PS) plastic waste into liquid fuel by the pyrolysis process, currently, especially in Surabaya, a lot of waste, 13% - 14% is plastic. The results of the sample from this study are to distinguish the temperature of the steam entering the condenser and also the temperature of the water in the condenser. And what will later be tested is that the oil from the plastic is close to the type of gasoline or diesel. The results of this study found that the optimum temperature to get a lot of results in 1 kg of plastic type Polyethylene (PET) is with a steam temperature of 142°C and a time of 90 minutes, while the type of plastic Polypropylene (PP) with a vapor temperature of 180°C and plastic type Polystyrene (PS) with a vapor temperature of 100°C and a condenser temperature of 15°C. The amount of oil produced by Polyethylene (PET) plastic at that temperature is 40 ml. while the plastic type Polypropylene (PP) the amount of oil produced is 100 ml. and this type of polystyrene (PS) plastic can produce 20 ml of oil. This result means that it is worth 75% of the weight of the plastic that has been processed. Meanwhile, the yield of this oil is close to the premium type.. Keywords: plastic waste, pyrolysis, liquid fuel